Dampak Media Sosial terhadap Seni Budaya - Dwinita Tiara Ningrum (Program Studi Desain Komunikasi Visual, Fakultas Sains dan Teknologi, Universitas Ma Chung, 2025)
Social media has significantly changed the landscape of art and culture. This article examines how social media plays a role in shaping the production, distribution, and appreciation of art using Pierre Bourdieu’s perspective, particularly the concepts of cultural capital, social capital, and the art scene. Using a qualitative method based on literature study, this article finds that social media algorithms act as ‘digital curators’ who determine the exposure of artworks. Artists who have high social capital are more likely to gain recognition than those who rely solely on cultural capital. This creates a new dynamic in the contemporary art ecosystem. This study provides insights into how artists can utilize social media without losing the aesthetic value and originality of their work.